2022
DOI: 10.3390/f13091420
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Niche Overlap and Prediction of the Potential Distribution of Two Sympatric Ficus (Moraceae) Species in the Indo-Burma Region

Abstract: Climate change is a major factor influencing the species distribution and population diversity of living creatures. In this study, the ecological niche model (ENM) MaxEnt was used to evaluate habitat suitability and predict potential habitats of two sympatric fig species, i.e., Ficus squamosa and F. heterostyla, in the Xishuangbanna region of China. Results indicated that mean diurnal range, isothermality, cation exchange capacity (at pH 7), and temperature seasonality were key variables influencing habitat su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The lower levels of genetic diversity observed in the four southeast F. heterostyla populations included in cluster 1 may result from the more fragmented habitats of Thailand they occupy. Ecological niche modeling of F. heterostyla indicated that habitat loss and fragmentation have been ongoing since the Last Glacial Maximum and are projected to continue into future decades, especially in southeast Thailand ( Fungjanthuek et al., 2022 ). The figs of F. squamosa are close to the ground or at water level (even below water) and restricted to riverine habitats ( Liu et al., 2015a ; Pothasin et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower levels of genetic diversity observed in the four southeast F. heterostyla populations included in cluster 1 may result from the more fragmented habitats of Thailand they occupy. Ecological niche modeling of F. heterostyla indicated that habitat loss and fragmentation have been ongoing since the Last Glacial Maximum and are projected to continue into future decades, especially in southeast Thailand ( Fungjanthuek et al., 2022 ). The figs of F. squamosa are close to the ground or at water level (even below water) and restricted to riverine habitats ( Liu et al., 2015a ; Pothasin et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with populations located nearer to equatorial regions, climatically marginal pollinator populations, similar to island populations ( Kusumi et al., 2012 ), are more vulnerable to extinction or temporary absence, and/or a reduction of host availability. Recent evidence indicates that southwest China represents the northern boundary of suitable habitats for the two targeted Ficus species ( Fungjanthuek et al., 2022 ). The present data corroborate these hypothesized predictions evinced by nuclear microsatellite hybridization peaking in northern marginal areas and decreasing towards low latitudes.…”
Section: Discussionmentioning
confidence: 99%